A forgotten subspecies of the land snail species Arianta arbustorum from a Pleistocene refuge in the Western Alps. (8th June 2021) - Hausdorf, Bernhard; Walther, Frank
ABSTRACT: Alpine Arianta populations from the Biellese Alps in Italy are characterized by imperforate, thin-shelled, dark brown shells without or with sparse light spots that resemble widespread phenotypes of Arianta arbustorum arbustorum found in calcium-deficient areas. Therefore, they were not considered a distinct taxon. However, molecular phylogenetic analyses show that they belong to a group of subspecies of A. arbustorum from the Western Alps and the Pyrenees. We classify them as a distinct subspecies, Arianta a. doriae (Paulucci, 1878), which reduces the geographical gap between the western group of subspecies of A. arbustorum and the Eastern Alps where Arianta originated. This subspecies survived the glacials in a peripheral mountain refuge at the southern margin of the Biellese Alps.